Manajemen Kearsipan Elektronik Pada Dinas Perpustakaan Dan Kearsipan Provinsi Sulawesi Tengah - Maulidianti, Deva Jianika; Haris, Subhan; Hamid, Nurhayati (JPS: Journal of Publicness Studies, 2026)
This study aims to determine how Electronic Records Management is implemented at the Library and Archives Office of Central Sulawesi Province. This research uses the theory of Read, Smith, and Ginn which explains that the records life cycle consists of four stages, namely Creation and Storage, Distribution and Use, Maintenance, and Disposition. This study employed a qualitative research method using observation, interviews, and documentation as data collection techniques, as well as the data analysis model of Miles, Huberman, and Saldana. The results of the study indicate that the Library and Archives Office of Central Sulawesi Province has implemented the Integrated Dynamic Archival Information System application (SRIKANDI). Electronic Records Management at the Library and Archives Office of Central Sulawesi Province through the use of the SRIKANDI application has generally been carried out properly. However, it has not been fully optimized because there are still several obstacles, such as some human resources who do not fully understand how to use certain features available in the SRIKANDI application. Another obstacle is network problems; when the network connection is unstable during the use of the application, work performance is disrupted and slows down the process. This study concludes that Electronic Records Management at the Library and Archives Office of Central Sulawesi Province has been implemented properly, including the process of record creation, adequate storage, easy access and use, maintenance through data backup and protection, and disposition through the use of Records Retention Schedule (JRA/Jadwal Retensi Arsip).